Pembiayaan UMKM Bank Umum Syariah di Indonesia Ditinjau dari Dana Pihak Ketiga (DPK) dan Non Performing Financing (NPF) - Fadilah Sari Siregar; Ismi Affandi; Diena Fadhilah (Jurnal Bilal: Bisnis Ekonomi Halal, 2021)
This research was conducted to determine the effect of third party funds and non- performing financing on the allocation of UMKM financing at Islamic Commercial Banks for the January 2016-December 2019 period. The dependent variable in this study is the allocation of UMKM financing, while the independent variable consists of third parties and non-performing financing. This research method is quantitative using secondary data with a sample of Islamic banking statistics during the period January 2016 to December 2019 totaling 48 samples (data). The analysis used in this study is multiple linear regression analysis which is processed with SPSS 25. The results of this study indicate that third party funds and non-performing financing simultaneously have a significant effect on the allocation of UMKM financing. Meanwhile, the results of the research partially show that third party funds have a positive and significant effect on the allocation of UMKM financing and non-performing financing has a negative and insignificant effect on the allocation of UMKM financing. Penelitian ini dilakukan untuk mengetahui pengaruh dana pihak ketiga dan non performing financing terhadap alokasi pembiayaan UMKM pada Bank Umum Syariah Periode Januari 2016-Desember 2019. Variabel dependen dalam penelitian ini adalah alokasi pembiayaan UMKM, sedangkan variabel independen terdiri dari pihak ketiga dan non performing financing. Metode penelitian ini adalah kuantitatif dengan menggunakan data sekunder dengan sampel dari statistik perbankan syariah selama periode Januari 2016 sampai dengan Desember 2019 sejumlah 48 sampel (data). Analisis yang digunakan dalam penelitian ini adalah analisis regresi linier berganda yang diolah dengan bantuan alat spss 25. Hasil penelitian ini menunjukkan bahwa dana pihak ketiga dan non performing financing secara simultan berpengaruh signifikan terhadap alokasi ketiga memiliki pengaruh positif dan signifikan terhadap alokasi pembiayaan UMKM dan non performing financing memiliki pengaruh negatif dan tidak signifikan terhadap alokasi pembiayaan UMKM .